High-Performance Solid Composite Polymer Electrolyte for all Solid-State Lithium Battery Through Facile Microstructure Regulation - Yang, Jingjing; Wang, Xun; Zhang, Gai; Ma, Aijie; Chen, Weixing; Shao, Le; Shen, Chao; Xie, Keyu (Frontiers in Chemistry, 2019)
Solid composite polymer electrolytes are the optimal candidate for all solid-state lithium batteries, because of their enhanced ionic conductivities, long-life cycle ability and compatibility to lithium anode. Herein, we reported a kind of solid composite polymer electrolyte comprised of poly(ethylene oxide), graphitic-like carbon nitride and lithium perchlorate, which was prepared by a facile solution blending method. Microstructure of the solid composite polymer electrolyte was regulated by thermal annealing and interaction among components and was characterized by XRD, DSC, FTIR-ATR and ROM. The obtained solid composite polymer electrolyte achieved an ionic conductivity as high as 1.76*10-5 S cm-1 at 25oC. And the electrochemical stable window and the lithium ion transference number, t+, were also obviously enhanced. LiFePO4/Li solid-sate batteries with as-prepared solid composite polymer electrolyte presented a high initial discharge capacity of 161.2 mAh g−1 and superior cycle stability with a capacity retention ratio of 81% after 200 cycles at 1C at 80oC. The above results indicates that the thermal annealing treatment and g-C3N4 as a novel structure modifier is crucial for obtaining the high-performance composite solid polymer electrolytes used in the all solid-state lithium battery.